2014
DOI: 10.3810/pgm.2014.07.2780
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Subjective Effects of Extended-Release Versus Immediate-Release Oxycodone/Acetaminophen Tablets in Healthy Nondependent Recreational Users of Prescription Opioids: A Randomized Trial

Abstract: This phase 1 study conducted in the United States was not registered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…IR/ER OC/APAP had lower and delayed positive subjective effects compared with IR OC/ APAP, in equal and single doses of intact and crushed tablets [12]. Moreover, crushed IR/ER OC/APAP tablets produced lower and delayed positive subjective effects compared with intact IR/ER OC/APAP tablets [12]. A limitation of this trial and the current study is the assumption that encapsulation of the crushed tablets would not meaningfully affect the absorption or subjective effects of the study drugs.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…IR/ER OC/APAP had lower and delayed positive subjective effects compared with IR OC/ APAP, in equal and single doses of intact and crushed tablets [12]. Moreover, crushed IR/ER OC/APAP tablets produced lower and delayed positive subjective effects compared with intact IR/ER OC/APAP tablets [12]. A limitation of this trial and the current study is the assumption that encapsulation of the crushed tablets would not meaningfully affect the absorption or subjective effects of the study drugs.…”
Section: Discussionmentioning
confidence: 84%
“…IR/ER OC/APAP had lower and delayed positive subjective effects compared with IR OC/ APAP, in equal and single doses of intact and crushed tablets [12]. Moreover, crushed IR/ER OC/APAP tablets produced lower and delayed positive subjective effects compared with intact IR/ER OC/APAP tablets [12].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous research in recreational abusers of prescription opioids has demonstrated that IR/ER OC/APAP tablets have lower attractiveness for abuse compared with IR OC/APAP tablets, crushed or intact, in single, equal, orally administered doses, based on positive subjective effects 17 . Importantly, this study assessed the ease with which IR/ER OC/APAP tablets can be tampered to facilitate snorting and injection because its comparator (IR OC/APAP) is abused by these means, although more commonly through oral intake of intact tablets.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of recreational users of prescription opioids, IR/ER OC/APAP tablets were found to be less attractive for abuse compared with IR OC/APAP tablets on the basis of positive subjective drug effects when administered orally as single, equal doses, in intact and crushed states 17 .…”
Section: Introductionmentioning
confidence: 99%